Impulse Buying Behavior Of Skincare Products On The Marketplace In Gen Z - Najla, Khansa Musyaffa; Hardi, Kurnia; Azizah Hidayat, Zahra; Nurlena Oktaviani, Siti; Purnama, Indah (International Student Conference on Business, Education, Economics, Accounting, and Management (ISC-BEAM), 2025)
This day, Generation Z has a strong interest in the use of beauty products in their self-improvement efforts. The rise of skincare trends along with the development of the cosmetic product market has a real impact on consumer behavior. The purpose of this study is to analyze the phenomenon of impulse buying in Generation Z on skin care products. This research uses a mixed method. SEM- PLS was used to quantitatively analyze the relationship between impulse buying behavior and hedonistic consumption trends, positive emotions, and skincare practices. In addition, NVivo was used to qualitatively investigate the influence of advertising, packaging aesthetics, and social media use. The interim findings of this study indicate that emotional factors, product promotion, and product visual appeal have a significant influence on impulse purchase behavior.